Simulation of Hot Rolling by Cellular Automata - Hegyes, Tibor; Barkóczy, Péter; Stefán, V. M. (International Journal of Engineering and Management Sciences, 2020)
Our research is focusing to one of the most complex and important production step of flat rolled products that is the simulation of hot rolling. During hot rolling two phenomena as work hardening and the process of regeneration of crystals has strong influence for physical properties of microstructure of aluminium alloys. It needs to be taken into account in case of rolling technology steps and development. When we talk about aluminium the dynamic softening in fact it is dynamic recovery that is followed by dynamic recrystallization. It goes in the same order of magnitude rate. But in steels the recovery has only a minor effect. Hot rolled and newly modified grain structure is influenced by these dynamic phenomena. Hot rolled grain structure goes through significant changes under further production steps like cold rolling and heat treatments. But aside from these intermediate production steps the microstructure that we get after hot rolling has significant effect for mechanical and grains structure of the final flat rolled product. Proper technology planning is essential that for cellular automata simulation method can ensure useable and good solution for the simulation of recrystallization.